Public service and good governance for the twenty-first century - Perry, James L.; Volcker, Paul A. (University of Pennsylvania Press, 2020)
Featuring essays from thought leaders in public administration, Public Service and Good Governance for the Twenty-First Century offers insights into the governance challenges facing the nation--from diminished capacity to the failure to meet expectations for reform--and recommendations for how civic institutions and leaders might respond.